Identifikasi Fungi Mikoriza Arbuskula (FMA) pada Mangga Lokal Indramayu - Faisal Al asad; Fadhillah Laila; Fina Dwimartina (Universitas Wiralodra, 2022)
Mango (Mangifera indica L.) is one of Indonesia's leading horticultural commodities. The island of Java is the national center for mango production. Mango production in West Java is one of the largest in Indonesia. The Indramayu region is the largest mango production center in West Java. Demand for this commodity is increasing, especially exports, while mango production in the last five years has fluctuated. The way to maintain optimal and sustainable mango production is by using fertilization. One of the fertilization efforts that can be done is with Arbuscular Mycorrhizal Fungi (AMF). The presence of AMF in host plants can help the uptake of nutrients, especially phosphorus which is very important in growth, especially in the generative phase of plants. However, not all AMF can be symbiotic with plants. Therefore, it is necessary to explore and identify AMF for its utilization. This study aimed to obtain information on the diversity of AMF in local mangoes from Indramayu. This research was conducted in Jatibarang District, Indramayu with a research time of 12 months and started after the rainy season. The results showed that two AMF genera were found in the local mango rhizosphere of Indramayu, namely the genus Glomus and Acaulospora. The number of AMF spores found per 20 g of soil was 37.67 in Lobener Village, 31.67 in Jatisawit Village, and 42.33 in Krasak Village. AMF colonization in Lobener Village was 34.44%, Jatisawit Village 23.33%, and Krasak Village 33.33%.